Evaluation of prevalence of  32 mutation in CCR5 gene in breast cancer patients in Rafsanjan city - Mohammad Kazemi Arababadi (Journal of Mazandaran University of Medical Sciences, 2009)
(Received 24 August, 2008; Accepted 21 May, 2009)AbstractBackground and purpose: Chemokines and their receptors are expressed in different types of malignancies. CC chemokines MIP-1 (CCL3), MIP-1 (CCL4) and RANTES (CCL5) is believed to be anti-tumor and also aid to the metastasis in tumor microenvironment. CCR2 and CCR5 are special G-protein receptors for these chemokines. Due to the important role of CCR5 chemokine receptor in tumor biology, this project is designed to examine  32 mutation in CCR5 gene regards breast cancer.Materials and methods: This experimental study was performed during 2007-8 on 100 healthy adults and 36 breast cancer patients by Gap-PCR. The demographic information also was collected by questionner and t-test Chi-square was used for statistical analysis of data.Results: Our results showed that none of breast cancer patients had CCR5- 32 mutation while 3 (3%) cases of controls had heterozygotic form of this mutation.Conclusion: Our results showed that there is not any CCR5- 32 mutation in patients. Therefore, it appears that this mutation don’t play any role in breast cancer.J Mazand Univ Med Sci 2009; 19(70): 49-53 (Persian)